2010
DOI: 10.1093/annonc/mdp498
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase III trial comparing docetaxel plus epirubicin versus docetaxel plus capecitabine as first-line treatment in women with advanced breast cancer

Abstract: The DE and DC regimens have similar efficacy but different toxicity. Either regimen can be used as front-line treatment of ABC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…Taxanes – paclitaxel and semisynthetic docetaxel (DT) – are approved as first-line treatment for non-small cell lung cancer (NSCLC) [6,7], breast [8,9] and ovarian [10] carcinomas and are also used in the treatment of numerous other malignancies [11,12,13,14,15]. Paclitaxel is a natural alkaloid isolated from Taxus brevifolia, whereas DT is a semi-synthetic compound produced from 10-deacetylbaccatin III found in Taxus baccata [16].…”
Section: Introductionmentioning
confidence: 99%
“…Taxanes – paclitaxel and semisynthetic docetaxel (DT) – are approved as first-line treatment for non-small cell lung cancer (NSCLC) [6,7], breast [8,9] and ovarian [10] carcinomas and are also used in the treatment of numerous other malignancies [11,12,13,14,15]. Paclitaxel is a natural alkaloid isolated from Taxus brevifolia, whereas DT is a semi-synthetic compound produced from 10-deacetylbaccatin III found in Taxus baccata [16].…”
Section: Introductionmentioning
confidence: 99%
“…In the second trial, with a superiority design unlike the non-inferiority design of MAMMA-3, the 2 treatment regimens were almost identical to those evaluated in ERASME-4, except that the capecitabine dose was 950 mg/m 2 b.i.d. instead of 1,000 mg/m 2 [4]. As with ERASME-4, the primary endpoint was not met, although arguably the statistical design was based on unrealistic assumptions: to increase median time to progression from 9 months with ET to 14 months with XT.…”
Section: Discussionmentioning
confidence: 99%
“…The combination was associated with a relatively high incidence of toxicity, particularly hand-foot syndrome and gastrointestinal toxicities, leading to frequent dose modification or treatment interruption. More recently, the XT combination has been tested in the first-line setting, typically using a lower capecitabine dose in combination with docetaxel [4,5]. Three phase III trials compared first-line XT with alternative docetaxel-containing doublets in HER2-negative MBC [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients never exposed to taxanes, the combination of taxanes plus antimetabolites is an attractive option: two randomized trials have shown a higher ORR, longer TTP, and longer OS time for the combination of docetaxel plus capecitabine versus docetaxel alone and for paclitaxel plus gemcitabine versus gemcitabine alone [60,61]. Another phase III randomized trial tested the combination docetaxel plus capecitabine versus docetaxel plus gemcitabine, showing no difference in efficacy with different tolerability profiles [62]. The incorporation of antiangiogenic agents is an attractive tool for this subset of patients who lack the benefits of other targeted agents.…”
Section: Metastatic Breast Cancermentioning
confidence: 99%